2023
DOI: 10.1101/2023.02.13.528362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BOLD response is more than just magnitude: improving detection sensitivity through capturing hemodynamic profiles

Abstract: Typical FMRI analyses assume a canonical hemodynamic response function (HRF) with a focus on the overshoot peak height, while other morphological aspects are largely ignored. Thus, in most reported analyses, the overall effect is reduced from a curve to a single scalar. Here, we adopt a data-driven approach to HRF estimation at the whole-brain voxel level, without assuming a profile at the individual level. Then, we estimate the BOLD response in its entirety with a smoothness constraint at the population level… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…Here, we used a spectral analysis that made no assumptions about the detailed shape of the BOLD signal changes. In line with our results, recent work that estimates the BOLD response directly from the signal ( 28 ), permitting flexibility of hemodynamic profile and shapes, revealed hemodynamic activity in white matter that was not found when using the canonical gray matter hemodynamic response function. Similar approaches that relax the overly strict response models may be necessary to improve detection sensitivity in white matter.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we used a spectral analysis that made no assumptions about the detailed shape of the BOLD signal changes. In line with our results, recent work that estimates the BOLD response directly from the signal ( 28 ), permitting flexibility of hemodynamic profile and shapes, revealed hemodynamic activity in white matter that was not found when using the canonical gray matter hemodynamic response function. Similar approaches that relax the overly strict response models may be necessary to improve detection sensitivity in white matter.…”
Section: Discussionsupporting
confidence: 92%
“…For example, previous studies have reported white matter BOLD signal responses to tasks and at rest ( 13 16 ), relationships between white matter signals and the gray matter regions to which they connect ( 17 19 ), alterations of white matter BOLD signal in disease/disorder ( 20 25 ), and finally, robust, reproducible network properties of white matter BOLD signals ( 18 , 26 ). Importantly, recent reports have confirmed that white matter responses to stimuli are similar to, but different from, those in gray matter ( 13 , 14 , 27 , 28 ), generally indicating a slower response, smaller percent signal change, and variation across regions ( 29 ). Together, the explicit removal of white matter BOLD signal as a nuisance regressor ( 30 ), inaccuracies in modeling white matter BOLD response functions ( 28 ), and decreased detection sensitivity due to low SNR, has made white matter a blind spot in the fMRI literature ( 30 ).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This concept has been proposed by Spencer et al (2020), but only lobe‐level correlations were considered due to current computation power limitations; (4) although the adapted four HRF process considered the variability of HRF shapes across brain regions and balanced fitting accuracy and generalizability, there are more flexible approaches that do not require predefined HRFs. For instance, the HRF deconvolution approach with regularization on the smoothness of the HRF can directly estimate the HRF from data (Chen et al, 2023; Cherkaoui et al, 2021; LeVan et al, 2010; Lu et al, 2006, 2007). This might be more effective for our application, considering that the variability of HRF shapes related to epilepsy discharges might not be fully encompassed by the four HRFs; (5) when comparing the presurgical evaluation performance with our previous study that employed a voxel‐wise approach involving a mixed‐effects model for within‐ and between‐run variability of the BOLD responses, an improvement was observed primarily in specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The canonical HRF convolution assumes standard time-to-peak values de ned by the HRF and does not consider the brain region nor the state of vigilance. However, the time-to-peak and the shape of the HRF BOLD response might differ between brain regions and for different subjects (Handwerker et al, 2004;Rangaprakash et al, 2018) with substantial HRF shape variability (Chen et al, 2023). Vigilance could also impact HRF responses due to excitability changes.…”
Section: Temporal Derivative Of Hrfmentioning
confidence: 99%